Radiofrequency Ablation versus Hepatic Resection for Small Hepatocellular Carcinoma: Systematic Review of Randomized Controlled Trials with Meta-Analysis and Trial Sequential Analysis - Xu, Xiao-Lin; Liu, Xiao-Di; Liang, Ming; Luo, Bao-Ming (Radiology, 2018)
Purpose To compare the benefits and harms of radiofrequency ablation (RFA) and hepatic resection (HR) and to test the consistency of currently available evidence. Materials and Methods PubMed, Embase, and the Cochrane Library were systematically searched for randomized controlled trials (RCTs) that compared the effects of HR and RFA for Barcelona Clinic Liver Cancer very early or early stage hepatocellular carcinoma (HCC). The primary outcome was overall survival, and secondary outcomes were recurrence rate, complication rate, and hospitalization duration. A random- or fixed-effects model according to the level of heterogeneity was applied. The meta-analysis was performed by using software, and trial sequential analysis (TSA) was performed. Results Five trials examining 742 patients were included in this study (sizes of trials: 161, 230, 168, 120, and 63 patients). The meta-analysis showed that RFA and HR had similar overall survival at 1 year (relative risk [RR], 1.39; 95% confidence interval [CI]: 0.36, 5.33; P = .63) and 3 years (RR, 1.40; 95% CI: 0.75, 2.62; P = .29), whereas RFA resulted in decreased overall survival compared with HR at 5 years (RR: 1.91; 95% CI: 1.32, 2.79; P = .001). The TSA showed that more trials were needed to control random errors. The incidence of overall recurrence was markedly higher and the hospitalization duration was significantly shorter in the RFA group than in the HR group, which was confirmed by TSA. Complications may have been less frequent in the RFA group, but TSA showed that additional trials were necessary to confirm this conclusion. Conclusion The indication for RFA as a primary treatment for patients who are eligible for HR with early stage HCC is unclear, and additional well-designed RCTs are needed. RSNA, 2017 Online supplemental material is available for this article.